Pengembangan Butir Soal HOTS: Tantangan dan Solusi Untuk Meningkatkan Kemampuan Analisis Siswa Pada Pembelajaran PAI - Hidayat, Rahmat; Rohmawati, Binti (Jumper: Journal of Educational Multidisciplinary Research, 2025)
HOTS questions in PAI learning can encourage students to think critically and apply Islamic teachings in real life contexts, while also overcoming the limitations of rote-based learning. This article aims to find the main challenges and solutions in developing HOTS questions to improve students' analytical skills in PAI learning. The research was carried out through a literature study approach by collecting data from various scientific journals that were relevant to the research study. The research results showed that the challenges in developing HOTS questions to improve students' analytical skills in PAI learning include; limited teacher knowledge, availability of time and resources, students' difficulties in adapting, unsupportive assessment systems, availability of references and example questions, variability in understanding concepts, lack of support from schools and less integrated knowledge. The proposed solutions include intensive training for teachers, increasing collaboration between teachers, implementing active learning methods, developing clear assessment criteria, providing references such as a HOTS-based question bank that is in accordance with PAI values ​​and utilizes technology in preparing questions. Innovation in PAI teaching through HOTS questions is not just an option, but an urgent need to give birth to a generation that thinks critically, creatively and adheres to religious values.